Factors influencing the adoption of artificial intelligence in healthcare: A study on the role of knowledge and benefits in clinical and managerial decision-making - Lopes da Costa, R.; Pereira, M.; Pereira, A. Â.; Canas, J.; Correia, R.; Dimande, C. (Businesses, 2025)
In recent years, Artificial Intelligence (AI) health projects have attracted significant investment, driven by a 50% annual increase in stored data. This growth has led to the development of AI tools that assist health professionals and managers in decision-making within clinical practice and healthcare management. This research seeks to identify key factors influencing the adoption of AI systems by health professionals and managerial staff, drawing on a sample of 100 respondents, of whom 61 are healthcare practitioners and 39 occupy management positions within the health sector. An extensive literature review and a statistical analysis using SmartPLS 3 were conducted. The findings suggest that the level of knowledge and perceived benefits positively impact the intention to implement AI tools. Interestingly, challenges during AI adoption do not hinder professionals. The study highlights the importance of integrating AI into healthcare professionals’ careers and emphasises the need for measures to enhance their understanding of AI algorithms. Increased knowledge fosters greater willingness to adopt AI systems, promoting improved decision-making in healthcare.